REKONSTRUKSI KONSEPTUAL EVALUASI PEMBELAJARAN AQIDAH AKHLAK BERBASIS RANAH KOGNITIF, AFEKTIF, DAN PSIKOMOTORIK - Rita Siska; Eka Putra Wirman; Hasnah (As-Sulthan Journal of Education, 2026)
Aqidah Akhlak learning plays a strategic role in shaping students’ faith and moral character in an integrated manner. However, evaluation practices in Aqidah Akhlak learning have predominantly emphasized the cognitive domain, while the affective and psychomotor domains have not been assessed proportionally. This article aims to conceptually reconstruct the evaluation of Aqidah Akhlak learning based on the integration of cognitive, affective, and psychomotor domains. This study employed a qualitative approach through a library research method by examining relevant scholarly literature, including books and peer-reviewed journal articles on learning evaluation and Islamic education. The findings indicate that the evaluation of Aqidah Akhlak learning should be designed comprehensively by assessing students’ understanding of aqidah concepts (cognitive), the internalization of religious values and attitudes (affective), and the practical manifestation of moral behavior in daily life (psychomotor). This conceptual reconstruction emphasizes that the success of Aqidah Akhlak learning should not be measured solely by knowledge acquisition but also by the formation of students’ attitudes and behaviors that reflect Islamic values. Therefore, holistic evaluation serves as a fundamental foundation for achieving the overarching objectives of Aqidah Akhlak education.